(untitled) (Bangladesh Journal of Medical Science, 2024)
Introduction: The most familiar kidney disease in children is nephrotic syndrome (NS), associated with dyslipidemia and causes various cardiovascular complications. Persistent hyperlipidemia can further raise difficulties of NS and relapse cases. Earlier diagnosis and appropriate intervention increase the possibility of saving other vital organs. Methods: An observational study was conducted with 85 children aged 2-15 years with a history of NS. The study group was divided into first NS and second-episode relapse cases. They were further subgrouped into Frequent Relapse NS (FRNS) and Infrequent Relapse NS (IFRNS). Fasting lipid profiles were performed among active sufferers with a follow-up after 4 weeks. Results: The male-to-female ratio was 1.93:1. In the first episode of NS, all lipid parameters were high in the acute phase and returned to normal during remission. In relapse cases, lipid parameters were significantly higher even in remission. Serum triglyceride and very low-density lipoprotein were significantly more elevated in the FRNS group than in the IFRNS. Low-density lipoprotein was increased considerably in FRNS. Mean high-density lipoprotein was also significantly lower in the FRNS group than in the IFRNS. Conclusion: Persistent hyperlipidemia is most typical among FRNS. Hyperlipidemia management is urgent to prevent among pediatric NS. Bangladesh Journal of Medical Science Vol. 23 No. 01 January’24 Page : 39-46